2018
DOI: 10.4103/ijabmr.ijabmr_420_16
|View full text |Cite
|
Sign up to set email alerts
|

Status of single nucleotide polymorphism of matrix gla protein gene (rs4236) in Nephrolithiasis: A preliminary study in indian population

Abstract: Background:Urine is a supersaturated solution with solutes in very high concentration. Matrix gla protein (MGP) is one of the proteins involved in inhibition of extracellular calcification. Among the various polymorphisms studied, polymorphism of SNP rs4236 in the MGP gene is found to have association with nephrolithiasis. We evaluated the significance of SNP rs4236 polymorphism in nephrolithiasis among the Indian population.Materials and Methods:The study was conducted in 2013 and 2014 among fifty participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…So far, there are few papers about MGP in stone-formers. One genetic variant of MGP, rs4236, has been significantly associated with higher risk of nephrolithiasis in several Asian populations (Indian [21], Japanese [22] and Chinese [10]), as well as in a Belgian cohort [11]. In addition, Wei et al also identified the polymorphs rs2430692 and rs2098435 that were associated to higher dpucMGP levels in stone formers [11].…”
Section: Discussionmentioning
confidence: 99%
“…So far, there are few papers about MGP in stone-formers. One genetic variant of MGP, rs4236, has been significantly associated with higher risk of nephrolithiasis in several Asian populations (Indian [21], Japanese [22] and Chinese [10]), as well as in a Belgian cohort [11]. In addition, Wei et al also identified the polymorphs rs2430692 and rs2098435 that were associated to higher dpucMGP levels in stone formers [11].…”
Section: Discussionmentioning
confidence: 99%